Alkynyl Thioethers in Gold‐Catalyzed Annulations To Form Oxazoles - Reddy, Raju Jannapu (Angew Chem Int Ed Engl, 2017)
Non‐oxidative, regioselective, and convergent access to densely functionalized oxazoles is realized in a functional‐group tolerant manner using alkynyl thioethers. Sulfur‐terminated alkynes provide access to reactivity previously requiring strong donor‐substituted alkynes such as ynamides. Sulfur does not act in an analogous donor fashion in this gold‐catalyzed reaction, thus leading to complementary regioselective outcomes and addressing the limitations of using ynamides.